Serum Raman Spectroscopy as a disease monitoring tool during treatment for colorectal cancer - SUSAN CHANDLER (2023)
Colorectal cancer is one of the most common cancers worldwide. There is a need for a biomarker with the ability to accurately detect disease status during treatment or follow up. Raman Spectroscopy is a technique using vibrational spectroscopy with the ability to accurately detect components such as carbohydrates, proteins, nucleic acids, lipids and more in blood serum. This thesis is focused on the investigation of Raman Spectroscopy as a technique for disease monitoring during treatment of colorectal cancer. Serum samples of patients undergoing surgical resection of colorectal cancer in the perioperative period, and patients undergoing chemotherapy treatment for colorectal cancer were analysed looking for changes during treatment related to disease. Changes in the serum were detected throughout the perioperative period, in regions associated with guanine, phenylalanine and tryptophan. Phenylalanine and tryptophan have previously been used in the diagnosis of colorectal cancer using Raman spectroscopy. Changes seen in regions associated with DNA and nucleotide bases may be linked to circulating tumour DNA during the perioperative period. Changes were seen in areas of the spectra associated with fatty acids and amino acids, that correlate with changes in metabolism related to the hallmarks of cancer. In patients undergoing chemotherapy, changes were noted in patients with disease recurrence prior to detection of recurrent disease by current methods. The serum spectra of patients with recurrence became more variable in the later treatment cycles than non-recurrence patients. Testing of the diagnostic RAMAN-CRC model showed potential for a machine learning model to predict disease status, with data from this study providing information to commence model building. This thesis concludes by discussing the clinical application of Raman spectroscopy and the potential role as a disease monitoring tool during treatment. As a more accurate and efficient tool than current techniques, serum Raman spectroscopy could have significant impact on patient outcomes.